Eyewitness to genocide : the Operation Reinhard death camp trials, 1955 - 1966 - Bryant, Michael S. 1962- (Legacies of war, 2014)
A subject for jurisprudence: from the Ulm Einsatzgruppen trial to the creation of the Ludwigsburg central office, 1956-1960 -- The queen of the dead: the investigation and trial of the Belzec death camp -- Who killed the Jews? The Treblinka investigation and trial -- Murdering star: the Sobibor investigation and trial -- Handy-dandy justice: Nazi crimes and the self-absolution of the West German Judiciary